The Information Content of Sudden Insider Silence - Hong, Claire Yurong; Li, Frank Weikai (Journal of Financial and Quantitative Analysis, 2019)
We present evidence of investors underreacting to the absence of events in financial markets. Routine-based insiders strategically choose to be silent when they possess private information not yet reflected in stock prices. Consistent with our hypothesis, insider silence following a routine sell (buy) predicts positive (negative) future returns, as well as fundamentals. The return predictability of insider silence is stronger among firms with a poor information environment and facing higher arbitrage costs, and a large fraction of abnormal returns concentrates on future earnings announcements. A long–short strategy that exploits insiders’ strategic silence behavior generates abnormal returns of 6% to 10% annually.